IMPROVING THE AGILITY QUALITY OF WRESTLERS THROUGH DYNAMIC GAMES (International journal of artificial intelligence, 2025)
This article analyzes method s for improving the agility quality of wrestlers through dynamic games. Wrestling is a sport that has a significant impact on physical and mental development, where agility, strength, and reaction ability are of great importance. Agility, or quick reaction, is one of the essential components necessary for wrestlers to achieve success. This article provides detailed information on the role of dynamic games in improving the agility quality of wrestlers, how such exercises can be incorporated into wrestling programs, and their effectiveness.